756 LONG-TERM OUTCOME AFTER ENDOSCOPIC SUBMUCOSAL DISSECTION FOR ENTIRE CIRCUMFERENTIAL CT1AN0M0 ESOPHAGEAL SQUAMOUS CELL CARCINOMA. (17th September 2021) - Inaba, Atsushi; Kadota, Tomohiro; Nishihara, Keiichiro; Sato, Daiki; Nakajo, Keiichiro; Yukami, Hiroki; Mishima, Saori; Sawada, Kentaro; Kotani, Daisuke; Fujiwara, Hisashi; Nakamura, Masaki; Hojo, Hidehiro; et al.
Abstract: : Endoscopic submucosal dissection (ESD) is the standard treatment for cT1a esophageal squamous cell carcinoma (ESCC), however its indication for the entire circumferential lesions is still controversial because of the risk of severe stricture after ESD. Therefore, several treatment options are performed based on physicians' choice, however, each clinical course is unclear. This study aimed to clarify the long-term outcome after ESD for patients with entire circumferential cT1aN0M0 ESCC, comparing with esophagectomy or chemoradiotherapy. Methods: Patients with entire circumferential cT1aN0M0 SESCC treated with ESD, chemoradiotherapy, or esophagectomy as the initial treatment between January 2010 and December 2016 in our institution were included. Patients who had a history of any malignancy at cStage II-IV within 5 years were excluded. The 5-year overall survival (OS), 5-year disease-free survival (DFS), stricture rate, refractory stricture rate (defined as requiring >6 dilations), curative resection (defined as pT1a without lymphovascular invasion and negative for vertical margin in the pathological evaluation) rate of ESD, and complete response rate of chemoradiotherapy were evaluated for each treatment. Results: Of the 48 eligible patients, 25/13/10 patients were performed ESD/chemoradiotherapy/esophagectomy as an initial treatment. Curative resections rate of ESD was 72%, and additional esophagectomy and chemoradiotherapy were performed in three and one patients with non-curative resection. Complete response rate of chemoradiotherapy was 100%, however, 4 patients had recurrence thereafter. No recurrences occurred after esophagectomy in all patients treated with esophagectomy. During median follow-up of 83 months, stricture and refractory stricture rate was 80/44% after ESD, 0/0% after chemoradiotherapy, and 20/10% after esophagectomy. The 5-year OS/DFS was 91/87% after ESD, 92/59% after chemoradiotherapy, and 90/90% after esophagectomy. Conclusion: While some patients required additional treatments due to non-curative resection, the long-term survival after ESD for circumferential cT1aN0M0 ESCC was similar as those after chemoradiotherapy or esophagectomy. In contrast, the stricture and refractory stricture rate after ESD was higher than others. Further investigation in a large cohort is necessary to clarify the indication criteria of ESD for patients with the lesion.